The Cassock Does Not a Monk Make. Or Does It? Fake and Real Monks from the Orthodox East in the Russian Empire (19th — Early 20th Сentury) - Chrissidis, Nikolaos (Istoriya, 2023)
Monastic tonsure of citizens of the Russian Empire abroad became a particularly complex issue during the latter half of the nineteenth century, when Mt. Athos became a favorite destination of those interested in assuming the monastic habit outside the empire. The Russian authorities sought to control and regulate such tonsures by establishing procedures for checking their validity, and by ruling out automatic recognition of them in the empire. Individuals who were tonsured as monks abroad manipulated or tried to manipulate such regulations in order to facilitate travel back and forth from the Russian Empire for their own purposes. The result was that the real and apparent ambiguities that such rules allowed for were exploited by both state authorities and by real or fake monks themselves. The essay seeks to offer some perspectives on this phenomenon by focusing on four cases preserved in archival records. © 2023 Ltd "Integration: Education and Science". All rights reserved.
Keywords: Mount Athos; St. Panteleimon Monastery; dept.his; fake monks; monasticism; peer-reviewed; tonsures abroad